Applicability of the complementary relationship of evapotranspiration for heterogeneous vegetation cover at boundary and plot scales - Chong Fu; Xiaoyu Song; Wanyin Wei; Qi Zhang; Lanjun Li; Xinkai Zhao; Pengfei Meng; Long Wang; Huaiyou Li (Journal of Hydrology: Regional Studies)
Study region: Two boundary-scale watersheds (Yangjiagou and Dongzhuanggou) and three typical vegetation plots [a single plantation, a mixed plantation, and a natural grassland] in the Loess Plateau. Study focus: The performance of different Generalized Complementary Relationships (four versions of GCR) in simulating actual evapotranspiration (ETa) at boundary (∼1 km2) and plot scales (much less than 1 km2) remains unclear, particularly under heterogeneous vegetation cover. Furthermore, the feasibility of using GCR directly to obtain accurate net ETa (ETan, the sum of soil evaporation and plant transpiration) through parameter calibration is investigated. The influence of timescale and vegetation diversity is also discussed. New hydrological insights for the region: Dynamic Scaling of the GCR could achieve high accuracy at boundary-scale watersheds (NSE=0.78) and different vegetation plots (NSE=0.79), indicating the universality and stability of the GCR, in line with the conclusions of previous large-scale studies. Reducing the timescale will decrease the GCR's simulation performance for both ETa and ETan. Interestingly, as vegetation heterogeneity increased, GCR's performance improved when simulating ETa but decreased when simulating ETan. Furthermore, using GCR to obtain ETan directly may generate bias near extreme points at a weekly timescale but becomes feasible at longer timescales. This study expanded recognition of GCR's performance under varying spatiotemporal scales and provided evidence for the possibility of simulating evapotranspiration components by the method.